XII. The Impact of Digital Economy Development of Countries Along “The Belt and Road” on China’s Economic Cooperation - Jiang, Ziang; Jia, Xingfei (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
Since the launch of the “Belt and Road” initiative in 2013, the digital economy has become a vital driver of its high-quality development. This study explores how the development of the digital economy in countries along the route influences China’s economic cooperation, particularly in terms of foreign direct investment (FDI). By analysing existing data and constructing a theoretical framework, the paper reveals that countries with higher digital economy development attract more Chinese FDI. This effect is especially significant for private firms, companies engaged in digital industries, and those with prior international experience. The findings highlight the strategic importance of digital connectivity in promoting cross-border investment and cooperation.